Neuroimaging of neonatal nociception - Baxter, L (2020)
Newborn infants undergo painful procedures during standard clinical care. However, pain assessment in non-verbal infants is challenging. Improving understanding of infant pain neurophysiology, including anticipating pain responses, is central to improving pain management. Magnetic resonance imaging (MRI) is an ideal technique for examining the structure and function of the infant pain system, allowing whole-brain coverage at relatively high spatial resolutions. However, major differences between the adult and infant brain necessitate the use of infant- optimised data analysis methods.